Revisiting fundamental welding concepts to improve additive manufacturing: From theory to practice - Oliveira, J. P. (2020)
The authors acknowledge Fundacao para a Ciencia e Tecnologia (FCT) for its financial support through the project UID/EMS/00667/2019. Fundo Regional para a Ciencia e Tecnologia and Projeto de I&DT for companies in copromotion SLM-XL, (Ref 3346), funded by Fundo Europeu de Desenvolvimento Regional (FEDER) through Programa Operacional Regional de Lisboa.